Analisis Strategi Komunitas Lyfe With Less dalam Mempromosikan Kampanye #Salingsilang terhadap Gaya Hidup Berkelanjutan di Era Media Sosial - Erwin Permana; Endah Pratiwi; Salsabila Nadia Nabila Sita; Yanita Ella Nilla Chandra (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The concept of sustainable living has increasingly influenced daily life, with communities adopting healthy habits, eco-friendly actions, and paperless practices. Lyfe With Less is one community actively promoting sustainability through the #SalingSilang campaign. This study analyzes their communication strategies to encourage sustainable lifestyles via social media. Using a qualitative descriptive method, data were collected through digital searches and observation. Findings reveal that social media functions as both an educational platform and a catalyst for social change. A multi-platform strategy ensures broad information dissemination, while exclusive memberships, such as those on Telegram, support deeper community engagement. Programs like the #SalingSilang Free Market and #BersalingSilang offer sustainable consumption alternatives. In 2024, 1,588 second-hand items were exchanged in Bandung, and 3,305 people participated in events across multiple cities. Innovations such as the Sustainable Journey Passport and subsidized shipping fees for online trades enhance public participation. Through these initiatives, Lyfe With Less has built a communication ecosystem that fosters minimalist and environmentally conscious lifestyles. Their approach effectively reduces overconsumption, raises waste management awareness, and demonstrates how social media can be a powerful tool for promoting sustainability.